Sections and features in newspapers published in Osijek from mid-19th to mid-20th century: overview of continuity and changes (Libellarium: journal for research in the field of information and related sciences, 2013)
The aim of the paper is to present the development of sections and features in newspapers published in Osijek from mid-19th to mid-20th century. The paper focuses on the establishment, development and shaping of sections, i.e. their setting, headings, name changes, change patterns, graphic and typographical solutions, etc. The research was conducted in the Newspaper Collection of the Museum of Slavonia. It was based on two criteria: years of publication and cultural importance, and included the following newspapers: Die Drau, Slavonische Presse, Narodna (Hrvatska) obrana and Hrvatski list.The research results prove that newspaper sections and features are only in the initial stage of development as a concept of newspaper content organization. Their names are mostly highlighted graphically as sub-headings on a page, often not systematically. The more important news is often not embedded in feature sections - features are a content element and not an organizational category. They often gather related information and occur only when there’s a sufficient amount of particular type of information.The paper takes a fresh look at investigating the history of Croatian newspapers, showing not only the development of sections and features, but also how research of this type can help reconstruct social change and the way it is reflected in daily newspapers, as we can assume that a new section or feature is introduced only when there is increased interest or sufficient attention of the public to a particular topic.
Keywords: Osijek; Osijek newspapers; newspaper sections and features; newspaper content organization